ANALYZING THE USE OF PERSONAL DEIXIS IN FIVE SHORT STORY BY OSCAR WILDE - Averedinta Delia Trisnanda (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2021)
AbstractA short story is one of the few publications that many enjoy. From children to adults, many choose to read short stories because they are simple and can being saved time, and short stories are entertaining and able to fill leisure time. There is one of the most frequent occurrences in a short story called deixis. Deixis is a word whose reference changes according to the context of the word, which can be based on the situation and the context when it is used (Parker, 1986:38). Person deixis one of the most frequently found kinds of a deixis can be found in a short story used to replace people or objects were used in a work either written or spoken. Oscar Wilde was a writer who also published his work in a short story. The short stories he made were mostly light stories that a child could read. The author has conducted this study to find out the number of the person deixis in Oscar Wilde's five short stories is The Happy Prince, The Devoted Friend, The Nightingale and the Rose, The Selfish Giant, and The Sphinx Without a Secret using a qualitative descriptive method. It is hoped that this research will provide more insight into the personal deixis both of its kind, numbers, and the meaning, especially in Oscar Wilde's short story for all the readers especially the students who are studying the deixis.